Profil Potensi Usaha dan Pengembangan Produk UMKM Pada Budidaya Rumput Laut Yang di Olah Menjadi Stik Rumput Laut Desa Panda, Kec.Palibelo, Kabupaten Bima - Lilis Putriyani; Siti Syarah Anggreani; Nur Annisah; Ayu Wulandari; Uswatun Hasanah; Aris Munandar (Universitas 45 Surabaya, 2024)
Panda village is a village that is rich in vegetable resource, so we are interested in doing data collection related to what things can build the potential of the village, there are so many things that must be developed in the panda village because of the potential that is owned by this, we provide information so that more people can know and can even see what potential the panda village has. This seaweed management activity as a regional specialty was carried out during the MBKM KKN-T activity for the Business Cooperative Management And UMKM in Panda Village. The aim of this service activity is to help create product innovations from local potential to help increase the income of the Panda Village community. Seaweed itself is one of the superior products of the local area which still lacks processing and knowledge of the benefits of seaweed itself. Seeing the existing opportunities, we developed seaweed such as seaweed sticks and conducted training on making attractive packaging with the aim of helping develop regional potential and increasing community creative businesses. collaborate with various parties.